Stretchable and Skin‐Attachable Electronic Device for Remotely Controlled Wearable Cancer Therapy. Issue 10 (2nd February 2023) - Ma, Xiaohui; Wu, Xiaotong; Cao, Shitai; Zhao, Yinfeng; Lin, Yong; Xu, Yurui; Ning, Xinghai; Kong, Desheng
Abstract: Surgery represents a primary clinical treatment of solid tumors. The high risk of local relapse typically requires frequent hospital visits for postoperative adjuvant therapy. Here, device designs and system integration of a stretchable electronic device for wearable cancer treatment are presented. The soft electronic patch harnesses compliant materials to achieve conformal and stable attachment to the surgical wound. A composite nanotextile dressing is laminated to the electronic patch to allow the on‐demand release of anticancer drugs under electro‐thermal actuation. An additional flexible circuit and a compact battery complete an untethered wearable system to execute remote therapeutic commands from a smartphone. The successful implementation of combined chemothermotherapy to inhibit tumor recurrence demonstrates the promising potential of stretchable electronics for advanced wearable therapies without interfering with daily activities. Abstract : A stretchable electronic patch is integrated into a self‐powered platform for skin‐attached administration of synergistic chemothermotherapy under remote commands from a smartphone. The successful inhibition of postoperative recurrence demonstrates the promising potential of stretchable electronic devices for wearable cancer treatment without interfering with daily activities.